INFLUENCE OF COLLECTION TIME ON NUTRIENTS AND MICROBIAL LOADS OF SOME FROZEN MARINE FISH SPECIES SOLD IN BICHI LOCAL GOVERNMENT AREA OF KANO STATE, NIGERIA - Ibrahim, Kasim Lawal; Bichi, Armaya'u Hamisu; Dauda, Akeem Babatunde; Salim, Ahmad Mahuta; Sadauki, Mustapha Amadu (FUDMA Journal of Sciences, 2025)
This study was carried to evaluate the influence of collection time on nutritional compositions and microbial loads of some frozen marine fish species; Clupea harengus, Scomber scombrus and Trachurus trachurus sold in Bichi local government area of Kano State, Nigeria. A total of 27 samples comprising of nine of each species were collected from the sampling station. The first collection was done upon the arrival of the stocks, the second collection was done four days after while the third collection was done when their stocks were about to finish. The samples were analyzed for proximate compositions, minerals, fatty acids, and microbial load. Results indicated that the highest crude protein content, 22.66% was recorded in S. scombrus from second collection. All the proximate composition parameters were affected by the species and collection time. S. scombrus had the highest calcium content, 1.40 mg/kg from second collection. All the mineral parameters were affected by the species except potassium, while collection time only affected potassium and iron. The highest free fatty acids content, 2.14% was observed in T. trachurus from third collection. S. scombrus recorded the highest Salmonella spp. count of 3.67 x 106cfu/g from third collection, Salmonella sp and total coliform counts were affected by the species while collection time affected all the microbial parameters except mold. These values were within the range for of safe and nutritionally balanced fish products. The study recommended S. scrombus as the best for human consumption due to its higher protein, least lipid and superior mineral composition.